Efeito dos anestésicos gerais inalatórios Sevoflurano e Isoflurano na exocitose de vesículas sinápticas em junção neuromuscular de diafragma de camundongo - Matheus de Castro Fonseca (2014)
Sevoflurane and isoflurane are halogenated anesthetics used for induction and maintenance of anesthesia. Despite being routinely used in clinical practice, their synaptic mechanisms of action are not clearly understood. In addition, these drugs also cause skeletal muscle relaxation during their administration in clinical procedures. This effect might be correlated with an inhibitory effect on the release of acetylcholine at the neuromuscular junction. Thereby, the aim of this work was to investigate and compare the presynaptic effects of sevoflurane and isoflurane at the mouse neuromuscular junction using optical techniques to visualize the recycling of synaptic vesicles. In the present study, diaphragm nerve-muscles preparations of mice were isolated and clusters of synaptic vesicles were labeled using the fluorescent vital dye FM1-43 to examine whether these volatiles anesthetics might interfere with the spontaneous and/or evoked exocytosis. Our data showed that both sevoflurane and isoflurane (0.45, 0.6 and 0.9 mM) did not evoke spontaneous exocytosis of synaptic vesicles. In addition, sevoflurane and isoflurane had no effect in inhibiting depolarization evoked by KCl (60 mM), a Na+-independent stimulus. However, sevoflurane and isoflurane significantly inhibited the depolarization evoked by 4AP (1mM) and veratridine (100 M), suggesting a putative action on sodium channels. Furthermore, the inhibition of FM1-43 destaining evoked by 4AP was greater under sevoflurane treatment compared to isoflurane. Exocytosis evoked by veratridine was inhibited by tetrodotoxin (1 M TTX) but no further inhibition was observed when TTX (1 M) was associated with either anesthetic. Nevertheless, a reduced TTX concentration (0.5 M) used together with 0.45 mM sevoflurane or isoflurane showed an inhibition similar to TTX (1 M) alone, indicating that both agents may target in voltage gated sodium channels. Thus, our data suggest that the volatile anesthetics sevoflurane and isoflurane inhibit exocytosis evoked by sodium dependent depolarization and it might act on sodium channels that are sensitive to TTX. These findings contribute to a better understanding of some clinical muscular aspects observed during administration of these halogenated volatile agents.